The Determinants of Price Rigidity in the UK: Analysis of the CPI and PPI Microdata and Application to Macrodata Modelling. (11th November 2018) - Zhou, Peng; Dixon, Huw
Abstract : This paper investigates price rigidity in UK consumer and producer markets, by estimating the hazard functions of price changes in microdata which are then used in macrodata modelling. We explore the mechanism of price setting using survival analysis in order to see what factors drive the observed price rigidity. We find significant effects of macroeconomic variables such as inflation and output, which should be purged off before calibrating any macroeconomic models. The microdata findings are then used to estimate and simulate a heterogeneous price setting model (generalised Calvo and Taylor), which improves the performance in matching macrodata persistence.